Effect of Growth Hormone Treatment on the Concentration of Selected Metabolic Markers in Girls With Turner Syndrome - Błaszczyk, Ewa; Gawlik, Jakub; Gieburowska, Joanna; Tokarska, Agnieszka; Kimsa-Furdzik, Małgorzata; Hibner, Grzegorz; Francuz, Tomasz; Gawlik, Aneta (Frontiers in Endocrinology, 2022)
Background As Turner syndrome (TS) predisposes to obesity and metabolic disorders, and their complications, such as cardiovascular diseases, are the main causes of shortened life expectancy in patients with TS, new metabolic markers that could serve as early predictors of dysmetabolic state are sought. Objective Assessment of MMP-1 (matrix metalloproteinase-1), MMP-2 (matrix metalloproteinase-2), MMP-9 (matrix metallopeptidase-9), BDNF (brain-derived neurotrophic factor), GDNF (glial cell line-derived neurotrophic factor), and VEGF (vascular endothelial growth factor) before the onset of growth hormone (GH) therapy and then during GH treatment as well as markers assessment during GH medication in girls with TS to establish marker stability and repeatability, and the impact of GH on markers concentration. Method The concentrations of circulating MMP-1, MMP-2, MMP-9, BDNF, GDNF, and VEGF were measured in nine girls with TS before the onset of GH therapy and then after at least 3 months of treatment period. Subsequently, markers concentration was determined in 17 girls during GH medication, with the first determination after at least a 3-month treatment period. The patients’ clinical and biochemical phenotypes were determined by weight, height, BMI, total cholesterol, HDL cholesterol, triglycerides, and glucose concentration. Results Comparison of markers concentration revealed a significantly higher concentration of MMP-2 in patients undergoing GH treatment (132.1 ± 42.05) than before the onset of therapy (105.0 ± 45.5, p=0.045). The values of the first measurement of VEGF in girls with TS undergoing GH therapy were significantly higher than those during the second measurement (30.9 ± 33.4 vs. 12.5 ± 11.7, p=0.029). There were no statistically significant differences between the measurements of the remaining markers concentration at any stage of the analysis. Conclusion Increase in MMP-2 concentration is visible during GH therapy in comparison to the pre-GH period in girls with TS which demands confirmation in subsequent tests. The role of VEGF requires further studies in the context of carbohydrate-lipid disturbances in girls with TS and its association with GH treatment.